PERAN LEMBAGA KEMAHASISWAAN DALAM PENGEMBANGAN SOFT SKILL MAHASISWA DI PERURUAN TINGGI SWASTA KOTA SAMARINDA - Dian Irma Aprianti; Eko Ravi Pratama; Andi Asrullah (University of Widya Gama Mahakam Samarinda, 2025)
This study aims to explore the role of student organizations in the development of soft skills among students at private universities in Samarinda. Using a qualitative descriptive approach, the data were collected through in-depth interviews and questionnaires distributed to student organization advisors at five private universities. The data analysis process included data reduction, presentation, and conclusion drawing. The findings show that active participation in student organizations significantly contributes to students’ soft skills development, especially in communication, leadership, and critical thinking. Student organizations serve as effective platforms for experiential learning, preparing students for the competitive job market.